P-403 Progesterone supplementation in frozen embryo transfer with hormonal replacement therapy is associated with a higher incidence of macrosomia. (30th June 2022) - Racca, A; Prats, P; Garcias, S; Alvarez, M; Coroleu, B; Polyzos, N.P
Abstract: Study question: Is there an impact of increased progesterone (P4) supplementation in hormone replacement therapy (HRT) frozen embryo transfer (FET) on obstetrical and neonatal outcomes? Summary answer: Increased P4 supplementation from the day of FET is associated with a significantly higher risk of macrosomia and a slightly higher risk of preeclampsia. What is known already: The most widely used method for endometrial preparation prior to FET is HRT, a sequential regimen with E2 and P4, which aims to mimic the endocrine exposure of the endometrium of the physiological cycle. However, in ∼40% of the patients undergoing HRT-FET cycles P4 levels before FET remain low and this may negatively affect pregnancy rates. Although recent prospective studies have shown that additional P4 supplementation in case of low serum P4 levels results in excellent reproductive outcomes, no data exist concerning the potential effect of this extra amount of P4 on obstetrical and neonatal outcomes Study design, size, duration: This is a single-centre, retrospective-observational study. Women undergoing HRT-FET treatment meeting the inclusion criteria were allocated to one of the 2 study groups according to the P4 supplementation. Group A (277) included women with adequate levels (>10.6 ng/ml) of P4, while group B (129) included women who received P4 supplementation due to inadequate levels of P4 (<10.6 ng/ml) on the day before the FET. All FET-HRT cycles were performed between February 2018 and December 2020. Participants/materials, setting, methods: All patients received micronized P4 (200 mg trice a day) starting six days prior to the FET and continued until 10 weeks of pregnancy. In case P4<10.6 ng/ml, P4 supplementation was initiated rather with 400mg more micronized P4 (15%) or with subcutaneous P4 (25mg more/once a day) (85%). Only patients with day5-embryos, known P4 levels prior to FET, known obstetrical and neonatal outcomes were included. Multivariable-logistic-model was fitted for macrosomia after adjusting for confounding variables. Main results and the role of chance: Patients' age at oocyte retrieval was 33.5 and 33.6 years (p = 0.833), while the age at delivery was 39.9 and 39.1 years (p = 0.099), respectively for groups A and B. The incidence of diabetes, hypertension, autoimmune diseases, coagulation, and kidney disorders was comparable for both arms. The mean value of P4 was 16 ± 7.7 and 8.2 ± 1.9, respectively for groups A and B. The mean gestational length was 39 weeks in both arms, with comparable rates of premature deliveries (delivery <37 weeks respectively 4.3% and 3.1 % for group A and B; p = 0.553). The rate of cesarean-section was 56% vs 47.3%, respectively for groups A and B (p = 0.103); there were 5 cases of pre-eclampsia in group A and 7 in group B (1.8% vs 5.4%; p = 0.059). The incidence of macrosomia was significantly higher in group B (6.1% vs 12.4%; P = 0.031). Similarly, group B had a higher rate of BGA-big for gestational age- babies (9.7 vs 15.5, p = 0.091). In terms of weight at delivery, pH, Apgar, and sex the two groups were comparable. Multivariable-logistic regression showed an association between macrosomia and P4 supplementation, adjusting for potential confounders such as sex, gestational diabetes, and weeks of gestation (OR 2.3, 95% CI 1.1-4.8). Limitations, reasons for caution: The main limitation of this study is its retrospective nature. Other potential limitations are the small sample size to detect obstetrical diseases with low incidence, such as preeclampsia. Furthermore, in our study population the PE rate is lower than in the general population, due to socioeconomic-conditions, race, and previous morbidity. Wider implications of the findings: P4-supplemented patients have a higher risk of macrosomia and a tendency for a higher risk of preeclampsia. However, more studies are needed to confirm the present exploratory findings and explain the possible physiological mechanisms underlying the association between progesterone supplementation on macrosomia and preeclampsia. Trial registration number: NA